Determination of the Running Mode of the Drilling Tool into the Borehole Taking into Account the Piston Effect - Aliyev, A.M. (Herald of Azerbaijan Engineering Academy, 2021)
When the drill string is run into the well, the load acting on the system can in some cases reach a dangerous level due to the load acting during pulling up. For example, if the weight of the casing being lowered into the hole is greater than the weight of the raised drill string, or when the drill string is lowered into the hole at high speed, very large dynamic forces can be generated that do not exist during pulling out. The only controllable parameters when running the drill string into the well for the length of one plug are the maximum value of the descent speed and the rate of deceleration. The relationship between these two parameters ultimately determines the efficiency of the lowering operation, which, in turn, is characterized by such factors as the operating mode of the equipment; compliance with technological requirements; physical load of the operator (driller). The goal is to determine the scientifically and technically sound mode of running the drilling tool taking into account the piston action. The permissible speeds of the drilling tool and the displacement of the string for the length of one plug during the well run, the speed of fluid movement in the annulus, were determined based on the equation of equilibrium of pressures in the well. Taking into account the turbulent regime of fluid movement in the annulus, the regime of safe running of the tool was determined to prevent hydraulic fracturing and ensure high-quality development of the productive horizon.